Beyond Wrapping: Investigation of the Design Processes of Personalising Gift-Wrapping - Chiba, Makiko (Auckland University of Technology, 2012)
This investigation explores the overall design processes of gift-wrapping within a Western context and is informed by the underpinning philosophical concept Ichigo Ichie (one encounter at a time) of gift exchanges in Japanese traditional wrapping rituals. Personalising the process of gift-wrapping is primary to the investigation, which is a visualisation of the immaterial effort to instil the emotions of the giver through the wrapping. The research intends to provide users with a new approach to gift-wrapping. It sustains the expression of immaterial feeling through a material object by incorporating a hands-on process that contributes to enhancing relationships in a material world. This will be examined by means of paper craft techniques.
Keywords: Gift-wrapping; Ichigo Ichie; Design process; Intimate relationship; Paper craft techniques; Personalisation